Energize the Base of the Pyramid! - Holländer, Robert; Verhoog, Mart (Logos Verlag Berlin, 2019)
In many countries of the Global South, energy infrastructure is holey, unreliable or simply not existent. This leads to different kinds of severe problems. Just to name a few: Family members, mostly women, spend hours every day to collect firewood for cooking. In many cases, they suffer under pulmonary diseases, because they have no access to clean cooking facilities. And companies are less productive without access to electricity.Students of the Joint International Master on Sustainable Development worked on energy access scale-up projects during their third semester at Leipzig University. In this semester, students are requested to work on an ''integration project'': integrating various aspects of sustainable development in a particular case study. The class of 2017 approached energy access from the interdisciplinary perspective of sustainable development, anchored however in the field of Economics and Management Science to ensure feasibility of their work.This present edition of Studies in Infrastructure and Resources Management looks at their work in two different energy access scale-up projects in the sub-Saharan countries Nigeria and Senegal.